Threat Detection Technique in Context to Mangrove Ecosystem of Indian Sundarbans - Goutam Roy Chowdhury; Goutam Sengupta; Arpita Saha; Samimul Islam; Sufi a Zaman; Abhijit Mitra (Annals of Marine Science - Peertechz Publications, 2017)
The mangrove ecosystem in the lower Gangetic delta is one of the most biologically productive and taxonmically diverse ecosystems of the tropics, which is threatened by a variety of stressors. The main threats operating in this fragile ecosystem are erosion, natural disasters (like cyclone, wave actions, tidal surges etc), over exploitation of natural resources, pollution, siltation, sea level rise etc. In this research, we have attempted to develop a mechanism to evaluate and rank the magnitude of threats based through collection of expert opinion from different groups of respondents. The respondents were categorised into five major classes namely policy maker, researcher, fisherman, agriculturist and local inhabitant. About 305 respondents belonging to this 5 categories were asked about the types of threats and their respective magnitude by ranking the threats between 1 to 6. Three different Composite Threat Scales were constructed for three sectors (western, central and eastern) of Indian Sundarbans as these three sectors have contrasting variations with respect to geographical features, salinity, biodiversity, and vulnerability of threats. The present approach of threat analysis can be a road map to identify the types of threats along with their magnitude in the mangrove ecosystem of the world. This scale can also be regulated because of regional settings, which would subsequently lead towards the path of conservation priority of natural resources.